Large bilateral lateral rectus recession in large angle divergence excess exotropia - Çelebi, S; Kükner, AS (Wichtig Editore, 2001)
PURPOSE. Classic teaching suggests that surgery for intermittent exotropia should be based on distance/near differences. True divergence excess exotropia should be treated with symmetric lateral rectus recession. The aim of this study was to investigate the effect of large bilateral lateral rectus (LR) recession in large-angle intermittent exotropia. METHODS. Thirty-three consecutive patients with large-angle divergence excess exotropia ranging from 50 to 65 (mean 56.7 +/- 6.3) prism diopters were treated with 8.0 to 9.5 mm (mean 8.8 +/- 0.7 mm) recession of both LR muscles. RESULTS. Successful alignment was achieved in 25 cases (76%) while residual exotropia was seen in eight patients (24%) within the limit of 15 prism diopters. Mean follow-up time was 28.5 +/- 8.4 (range 13 to 38) months. Abduction deficit due to this procedure was not seen in any case. CONCLUSIONS. We conclude that large bilateral LR recession is an appropriate surgical method for large-angle divergence excess exotropia.
XIIth Congress of the SOE -- JUN 27-JUL 01, 1999 -- STOCKHOLM, SWEDEN
Keywords: intermittent exotropia; divergence excess exotropia; large-angle exotropia; lateral rectus muscle; large bilateral lateral rectus recession